Comparison of Simple and Rapid Methods for Identifying Enterococci Intrinsically Resistant to Vancomycin - Hanson, Kevan L. (American Society for Microbiology, 1999)
Three different methodologies, reduction of litmus milk (LM) and acidification of arabinose (ARA), acidification of methyl-α-d-glucopyranoside (MGP), and rapid motility (RM), for differentiating isolates of Enterococcus casseliflavus and Enterococcus gallinarum (intrinsically vancomycin-resistant enterococci [IVRE]) from Enterococcus faecalis and Enterococcus faecium were evaluated. All 33 isolates of E. faecalis tested reduced LM within 4 h and were negative in all other tests, while the 53 isolates of E. faecium were ARA positive only. In contrast, 45 of 46 (98%) IVRE isolates examined (26 E. casseliflavus and 20 E. gallinarum isolates) acidified MGP, 41 of 46 (89%) were LM and ARA positive, and 45 of 46 (98%) were RM positive. Acidification of MGP was therefore the single most useful test for differentiating IVRE from vancomycin-resistant E. faecium and E. faecalis; however, a combination of LM-ARA and RM testing enabled the correct designation of organisms without the need for overnight incubation.